Javanese students' perception of desirability and helpfulness of types and valences of peer feedback. - Winarno, Alphonsus Rachmad Djati (Animo Repository, 1995)
This research identifies the kind of feedback the Javanese students prefer in getting feedback from peers as to improve their interaction with others. One hundred six male and female Javanese students of Soeggijapranata Catholic University and Sanata Dharma University were surveyed. The data were analyzed using the analysis of variance (ANOVA) and the least significant difference (LSD) analysis. The analyses revealed that the positive feedback was perceived as the most desirable and the most helpful. Negative feedback, on the other hand, was the least desirable and least helpful. Behavioral feedback and behavioral-emotional feedback were considered as superior to pure emotional feedback. Hence, there were valence effect and type effect. It was revealed that there were effects of combination of valence and type. Gender effect was only found in the interaction effect of feedback and gender in the perception of desirability.